Effectiveness of Online Mindfulness-Based Intervention on Depression in Pregnancy - Kundarti, Finta Isti; Titisari, Ira; Kiswati, Kiswati; Jamhariyah, Jamhariyah; Rahayu, Dwi Estuning (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The high prevalence of depression in developed and developing countries requires a relevant intervention to suppress its incidence. Mindfulness-based intervention is given online as a new complementary intervention that can help reduce symptoms of depression. This study aimed to determine the effectiveness of online mindfulness-based interventions in reducing depressive symptoms in pregnancy. This research method used a randomized control trial, with 66 participants consisting of the mindfulness-based Intervention (MBI) group of 33 participants and the control group of 33 participants. The MBI intervention was provided for eight weeks online. The study uses simple random sampling. Depression was assessed using DASS 42. Data were tested using the Mann-Whitney U Test and t-test and processed with SPSS version 23. The results showed that there was a significant decrease in depression levels in the online MBI group after being given intervention compared to the control group (7.55 ± 2.181 vs 11.00 ± 2.345) p=0.000. Mindfulness-based intervention online can reduce depressive symptoms in pregnant women, so that the intervention becomes a feasible, cheap and easy intervention for pregnant women in improving mental health. In the future, this research can develop other types of complementary interventions to improve maternal and fetal health.